To find alternative equivalent versions of the simple interest formula \( I = prt \), we can manipulate the formula to solve for \( p \), \( r \), \( t \), or verify the equivalence of different phrases. Here are the derived equations along with their explanations:
-
\( p = \frac{I}{rt} \)
- Rearranging the original equation \( I = prt \) gives \( p = \frac{I}{rt} \), which is correct.
-
\( I - rt = p \)
- This is incorrect. The equation rearranging from \( I = prt \) would not yield \( I - rt = p \).
-
\( I = trp \)
- This rearrangement is incorrect. While the equation is algebraically consistent with multiplication, it doesn’t represent the original context accurately.
-
\( I = p + rt \)
- This is incorrect. The original equation \( I = prt \) does not relate \( I \) as the sum of \( p \) and \( rt \).
-
\( t = \frac{I}{pr} \)
- Rearranging \( I = prt \) gives \( t = \frac{I}{pr} \), which is correct.
Therefore, the correct options representing an equivalent version of the simple interest formula are:
- \( p = \frac{I}{rt} \)
- \( t = \frac{I}{pr} \)